Color Stability Of Various Resin Sealants After Staining Protocol - Danila Dokuchayev; Margareth Rivas; Rafael Rocha Pacheco, DDS MDS PhD (Elsevier, 2024)
OBJECTIVES: Evaluate the color change in various resin sealants when activated by a multi-peak light-curing unit (LCU), in comparison to a flowable resin composite. METHODS: Four different resin sealants were evaluated: [HS] Helioseal® F Plus (Ivoclar Vivadent), [CP] Clinpro™ (3M™ Oral Care), [GS] Grandio Seal (VOCO GmbH), and [XT] Ultraseal XT™ Hydro (Ultradent Products Inc.). A flowable resin composite (3M™ Filtek™ Supreme Flowable Restorative, A2) was used as control. Using PVS, molds were made from custom 3D-printed models measuring 6.0mm in diameter and 2.0mm in height. Materials were inserted into the molds (n=5), covered by a Mylar® strip, pressed using a microscope slide, and light-activated for 20 seconds using a multi-peak LCU (VALO™ X, Ultradent) in standard mode. All specimens were wet-finished and polished using sandpaper (grits 600 and 1200). The L*, a*, and b* color parameters for each specimen were assessed on both white and black backgrounds using a clinical spectrophotometer (VITA Easyshade®, VITA Zahnfabrik). A staining protocol using black tea was applied. Each specimen was immersed for 24h at 37oC, rinse and dried, and subjected to a 5-minute ultrasonic bath in distilled water. Data was then collected, and ΔE calculated. Statistical analysis was carried out using GraphPad Prism 10.0.2, utilizing ANOVA with a preset alpha of 0.05. RESULTS: All evaluated resin sealants exhibited a ΔE greater than 11, in contrast to the flowable resin composite that was below 3.5. The b* parameter was most influenced, showing a trend towards yellowing (ordered as HS>XT>GS>CP>FT), followed by a decrease in the L* parameter indicating darkening (GS>XT≥HS≥CP>FT). Finally, the a* parameter experienced minor positive and negative variations. CONCLUSIONS: Resin sealants demonstrate higher susceptibility to staining than flowable resin composites. Black tea exposure led to a more yellow hue (increased b*) and a darkening effect (reduced L*) in resin sealants. IMPLICATIONS: Sealants are prone to color changes when exposed to the oral environment, more so than other composite materials or the tooth structure itself. Understanding how this color change occurs is crucial for accurately diagnosing a stained sealant rather than mistaking it for secondary caries. It is noteworthy that different sealants exhibit varying degrees of staining.